ANALISIS YURIDIS PERWALIAN ANAK KARENA PENCABUTAN KEKUASAAN ORANG TUA YANG TIDAK DIKETAHUI KEBERADAANNYA (STUDI PUTUSAN NO.1613/Pdt.G/2014/PA.Mdn) - HASIANI PUTRINTA DONGORAN (PREMISE LAW JURNAL, 2016)
There fore minors are at the mercy of parents, but parental authority can be revoked by the religious court this is due to negligence and no ready parents in taking care of their children, Issues of revocation of power of parents by the court is very interesting to study in a thesis, with the background of problems as follows, namely how the legal position of its parents are not known to exist, and what form of legal protection of children as a result of the revocation of parents set religious court, and how due to child-custody laws for the revocation of parents who are not known to exist (Study Of Religion Court Decision Number 1613 / PDT.G / 2014 / PA.Mdn). While legal protection against children forms due to the revocation power of parents who set namely religious courts religious Courts assign a guardian as Substitute notch the father and mather parents to review nurture and take care of the interests of the young everything. in addition to legal consequences the against child trust because revocation power of parents who is not known to exist (Study Of Religion Court Decision Number 1613 / Pdt.G / 2014 / PA.Mdn) That trustee appointed and by the religious court decided to replace the position differences parent power against his son the has repealed by justice religion because known to exist. Keywords : Child Custody, Parents’, Revocation Of Parents’ Authority